Nutritional effects of flooding due to unseasonably early monsoon rainfall in Bangladesh: a cross-sectional study in an ongoing cluster-randomised trial - Gabrysch, Sabine; Waid, Jillian; Wendt, Amanda; Müller-Hauser, Anna A. (The lancet. Planetary health, 2018)
Background: Subsistence farmers worldwide experience food insecurity and undernutrition and are particularly affected by natural disasters. In 2017, unseasonably heavy rains in Bangladesh in mid-April filled the northeastern floodplain early and destroyed the annual rice crop before it was ready to be harvested. We aimed to quantify the effect of this flood on food security and the dietary diversity of women and children in the area, describe families' coping strategies, and assess whether a dietary diversification programme could attenuate negative effects of flooding. Methods: This study is nested in the Food and Agricultural Approaches to Reducing Malnutrition (FAARM) cluster-randomised trial (NCT02505711) in rural Sylhet Division, Bangladesh, which is investigating the effect of a homestead food production programme on undernutrition. FAARM includes nearly 2700 young women in 96 villages, of which 48 villages were randomly assigned to the intervention and 48 are controls. We visited all trial participants every 2 months to collect data on diet, morbidity, and pregnancies. We also collected data on overall perceived effect of the flood on the household, coping strategies, and household food security roughly 6 months after the flooding event. We did multilevel regression analysis, adjusting for intervention allocation, to quantify the effect of the flood on food security and nutrition outcomes. This study is ongoing, and we will continue to collect data on diets and health. Findings: We interviewed 2405 women about the flooding, of whom 1335 (56%) reported that their families were affected by the flood to a great extent, whereas 505 (21%) reported that they were not affected at all. Of the 1577 families who usually grow rice and grew rice in 2017, 528 (33%) harvested at least as much as usual, whereas 445 (28%) expected a shortfall of 5 months or more of rice consumption compared with a usual year. Income losses were also reported by many households. At 6 months after the flood, only 722 (30%) of 2423 families were food secure and 356 (40%) of 901 women interviewed about their diet consumed an adequately diverse diet. Families with a large rice shortfall (5 months or more) had more than double the odds of food insecurity than did those with no shortfall (odds ratio 2·5, 95% CI 1·8-3·6), adjusting for baseline food insecurity and usual rice harvest. Dietary diversity among women in these families was 0·4 (95% CI 0·1-0·7) food groups lower than in families with no shortfall, adjusting for dietary diversity 1 year previously. The most commonly reported coping strategy among the families who perceived their livelihoods to be affected to a great extent was borrowing money (777 [58%] of 1335 families), mostly from outside lenders. Interpretation: Natural disasters exacerbate food insecurity and worsen dietary diversity among subsistence farmers. In a changing climate, natural disasters are becoming more frequent in Bangladesh and elsewhere. Funding: German Federal Ministry for Education and Research, UK Department for International Development, Dutch Ministry of Foreign Affairs, and the Alexander von Humboldt Foundation.